Mallarmé and the politics of literature Sartre, Kristeva, Badiou, Rancière - Boncardo, Robert (Crosscurrents (Edinburgh University Press), 2018)
With in-depth studies of Jean-Paul Sartre, Julia Kristeva, Alain Badiou and Jacques Rancir̈e, along with shorter analyses of Jean-Claude Milner and Quentin Meillassoux, Boncardo asks how Stéphane Mallarmé became so politically significant for left-wing French intellectuals.